Exploring job design as predictors of job performance at a Malaysian automobile company / Hadijah Iberahim ... [et al] - Iberahim, Hadijah; Shamsul, Anis Suraya; Azhar, Fara Athira; Aminuddin, Zakiah Hanim Aminuddin (Universiti Teknologi MARA, Perlis, 2020)
An organization must initiate adequate job design for desired job performance. A question arises on how a company could gain high job performance in a dynamic business environment and diverse background. This study examines the influence of four components of job design as predictors to job performance; job enrichment, job rotation, job enlargement and job simplification. While job design is proven to contribute to high job performance, some literature states its limitations. This study adopted a case study method to investigate issues faced by a leading automobile company in Malaysia. Primary data were collected through a distribution of questionnaires. A multiple regression model was used to explore the predictors of job performance. It was found that job rotation and job enlargement were significant to job performance, while the insignificant effect of job enrichment and job simplification needs to be reviewed. The results of the analysis were discussed in line with related literature. The study contributed to the new understandings on critical factors of job design that influence job performance in the support cluster of a manufacturing company.